Quantum Control for Nanoscale Spectroscopy With Diamond Nitrogen-Vacancy Centers: A Short Review - Hernández-Gómez, Santiago; Fabbri, Nicole (Frontiers in Physics, 2021)
Diamond quantum technologies based on color centers have rapidly emerged in the most recent years. The nitrogen-vacancy (NV) color center has attracted a particular interest, thanks to its outstanding spin properties and optical addressability. The NV center has been used to realize innovative multimode quantum-enhanced sensors that offer an unprecedented combination of high sensitivity and spatial resolution at room temperature. The technological progress and the widening of potential sensing applications have induced an increasing demand for performance advances of NV quantum sensors. Quantum control plays a key role in responding to this demand. This short review affords an overview on recent advances in quantum control-assisted quantum sensing and spectroscopy of magnetic fields.